Development of gait motor control: what happens after a sudden increase in height during adolescence? - Bisi, M. C.; Stagni, R. (BioMedical Engineering OnLine, 2016)
Background: Basic understanding of motor control and its processes is a topic of well-known high relevance. During adolescence walking is theoretically a well-achieved fundamental skill, having reached a mature manifestation; on the other hand, adolescence is marked by a period of accelerated increases in both height and weight, referred as growth spurt. Thus, this period was chosen as a controlled and natural environment for partially isolating one of the factors influencing motor development (segment growth). The aim of the study was to compare gait performance of growing and not growing male adolescents during walking in single task (ST) and dual task (DT), in order to study which are the modifications that motor control handles when encountering a sudden change in segment length.